2014
DOI: 10.1155/2014/152087
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation for Early-Stage Nonsmall Cell Lung Cancer

Abstract: This review examines studies of radiofrequency ablation (RFA) of nonsmall cell lung cancer (NSCLC) and discusses the role of RFA in treatment of early-stage NSCLC. RFA is usually performed under local anesthesia with computed tomography guidance. RFA-associated mortality, while being rare, can result from pulmonary events. RFA causes pneumothorax in up to 63% of cases, although pneumothorax requiring chest drainage occurs in less than 15% of procedures. Other severe complications are rare. After RFA of stage I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 58 publications
4
39
0
Order By: Relevance
“…Although our study consisted of limited number of patients with NSCLC, our overall survival outcomes were similar to those reports. LTP after RF ablation was reported to be higher than after sublobar resection and SBRT (14), which was similar to our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although our study consisted of limited number of patients with NSCLC, our overall survival outcomes were similar to those reports. LTP after RF ablation was reported to be higher than after sublobar resection and SBRT (14), which was similar to our study.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, in the review study of Hiraki et al (14), one-, two-, three-, and five-year overall survival rates after RF ablation of stage I NSCLC were reported as 78%-100%, 53%-86%, 36%-88%, and 25%-61%, respectively. In another previously published systematic review of RF ablation for lung tumors including 17 studies, Zhu et al (15) reported that one-, two-, and three-year survival rates ranged between 63%-85%, 55%-65%, and 15%-46%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, some patients cannot undergo surgery because of poor respiratory function, advanced age, or comorbid disease. Recently, radiofrequency ablation (RFA) of the lung for patients who are not surgical candidates has been reported to achieve comparable results to surgical resection [11][12][13][14][15][16][17][18][19]. However, the availability of this treatment in Japan and re- ports on its outcomes from this country are limited because of lack of coverage within the national health insurance system.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have shown that RFA was as effective as surgical resection in selected patients with primary pulmonary tumors (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%